2019
DOI: 10.1080/1331677x.2019.1663436
|View full text |Cite
|
Sign up to set email alerts
|

The inter-linkages between financial and economic development in the European Union Countries

Abstract: The paper has investigated the relationships between financial and economic development in the European Union countries using annual data over the period of 1998-2016. The authors have done this by looking at descriptive statistics and also by applying econometric methods. This study has combined different approaches prevailing in the scientific literature and contributed to understanding the importance of the interrelationship between the variables. The investigation has led to the conclusions as follows: (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Nonetheless, other studies validated the demand-following hypothesis that economic growth causes financial development (Ginevicˇius et al, 2019;Kassi et al, 2021). It stipulates that economic growth will lead to the emergence of financial products and institutions to meet the demand for financial services.…”
Section: Finance and Economic Growthmentioning
confidence: 95%
“…Nonetheless, other studies validated the demand-following hypothesis that economic growth causes financial development (Ginevicˇius et al, 2019;Kassi et al, 2021). It stipulates that economic growth will lead to the emergence of financial products and institutions to meet the demand for financial services.…”
Section: Finance and Economic Growthmentioning
confidence: 95%
“…The relevant empirical research uses multiplicative dummies to compare two distinct sub-periods before and after the crisis, where the results show that before crisis, financial development promoted economic growth, while after the crisis it hindered economic activity. The study of Ginevičius et al (2019) examined the relationship between financial and economic development in the countries of the European Union using annual data for the period 1998-2016, the authors did this by reviewing descriptive statistics and also by applying econometric methods. The Granger causality test showed that the authors found: (1) countries with an average GDP per capita indicator showed the highest level of financial development; (2) in Denmark, Portugal and Latvia, unidirectional causality has been discovered, from real GDP to financial development; (3) unidirectional causality running from financial development to real GDP has been found in Austria; (4) two-way causal links between financial and economic development have been identified in Luxembourg, France and the United Kingdom; (5) results from Finland, Germany, the Czech Republic, Slovakia, Croatia and Bulgaria supported the neutrality approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Air pollution is of particular concern in countries with former centrally planned economies (as in the case of Hungary), due to low energy efficiency and a relatively weak legislative framework [ 33 , 34 ]. Hungary has seen a decline in air pollution in recent years [ 35 ], but this is due to the collapse of former industrial structure rather than to conscious policy measures [ [36] , [37] , [38] ].…”
Section: Introductionmentioning
confidence: 99%